Gestione e trattamento delle fratture acetabolari - Pascarella, R.; Cerbasi, S.; Sangiovanni, P.; Fantasia, R.; Buharaja, R.; De Marco, R.; Riccardi, M.; Arduini, M. (Lo Scalpello - Journal, 2019)
MANAGEMENT AND TREATMENT OF ACETABULAR FRACTURESAcetabular fractures are complex lesions and they require anatomical surgical reduction in order to achievesatisfactory results in long-term follow-up. Some risk factors are associated with unfavourable results and haveconfirmed that older patients with acetabular fractures have worse outcomes than younger patients. Total hipreplacement after an acetabular fracture generally produces good clinical results; however, in some contexts it must becombined with correct stable fixation of the fracture. The type of fracture and overall patient conditions influence thechoice of the surgical technique and, consequently, the type of healing to lead to a satisfactory result.